Analyzing Satisfaction and Continuance Intention in Capital Market School Level 2 - Sahupriadi, Sahupriadi; Putro, Utomo Sarjono (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study analyzes factors influencing participant satisfaction and their continuance intention to enroll in the Level 2 Capital Market School (SPM) program in Indonesi. Despite the rising number of investors, the transition rate from Level 1 to Level 2 shows a decline, raising concerns about learner retention. Guided by the Expectation-Confirmation Model (ECM), this research examines the effects of Quality of Teaching, Institutional Offering, and Participant Motivation on participant satisfaction and their intention to continue. Using data collected from 163 SPM Level 1 participants in Bandung and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS), the study confirms that all three factors positively influence satisfaction, which in turn significantly impacts continuance intention. The findings highlight the mediating role of satisfaction in promoting ongoing engagement with capital market education. The results suggest that enhancing instructional quality, improving institutional support, and fostering participant motivation are key to increasing retention rates for advanced financial education programs. This research provides valuable insights for policymakers and educators aiming to strengthen investor education and support Indonesia’s growing capital market.